2020
DOI: 10.1016/j.nicl.2019.102132
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal EEG microstate analysis in drug-free patients with Parkinson's disease

Abstract: HighlightsWe have found that PD can be characterized by unique spatial microstate different from healthy controls, which may be related to the brain dysfunction in PD.The drug-free patients with PD show abnormal brain dynamics revealed by the regular changes of temporal microstate features in early PD and such temporal dynamics in microstates are correlated with motor function and cognition of the subjects.The obtained results may deepen our understanding of the brain dysfunction caused by PD, and obtain some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 52 publications
9
39
1
Order By: Relevance
“…Furthermore, the study results also showed that the PD groups (w/ and w/o ICD) exhibited weakened N2 and P3 peak amplitudes with respect to the HC group (c.f., Figure 4), which replicated early findings [14,32]. While previous studies mostly focused on EEG differences between different PD stages [33][34][35] or between PD vs. HC individuals [14,31,32], less effort has been devoted to assess PD patients against PD patients diagnosed with ICD. In order to address this issue, the present work conducted two sessions of the Go/NoGo task interleaved with the DA-pharmacological treatment for PD groups.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the study results also showed that the PD groups (w/ and w/o ICD) exhibited weakened N2 and P3 peak amplitudes with respect to the HC group (c.f., Figure 4), which replicated early findings [14,32]. While previous studies mostly focused on EEG differences between different PD stages [33][34][35] or between PD vs. HC individuals [14,31,32], less effort has been devoted to assess PD patients against PD patients diagnosed with ICD. In order to address this issue, the present work conducted two sessions of the Go/NoGo task interleaved with the DA-pharmacological treatment for PD groups.…”
Section: Discussionsupporting
confidence: 84%
“…The use of a nonmedicalgrade EEG-sensing platform is a harsh yet realistic setup, closer to a practical wearable-device for ubiquitous ICD monitoring. While most previous studies focused on the EEG/ERP distinction between PD patients and healthy subjects [14,31,32] or between different PD stages [33][34][35], the present work attempted to address whether ERP signatures can be regarded as neuro-markers reflecting the DA-triggered ICD adverse effect in PD patients. This work also contributes to the practical application of EEG by using a customized, cost-efficient EEGsensing setup rather than an expense laboratory-oriented product.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have reported that resting-state EEG microstates are altered in neuropsychiatric and neurodegenerative disorders, such as Alzheimer’s disease (Musaeus et al 2019 ; Smailovic et al 2019 ), Parkinson’s disease (Chu et al 2019 ), schizophrenia (Andreou et al 2014 ; Baradits et al 2020 ; da Cruz et al 2020 ; de Bock et al 2020 ; Giordano et al 2018 ; Kindler et al 2011 ; Koenig et al 1999 ; Lehmann et al 2005 ; Murphy et al 2020a ; Nishida et al 2013 ; Soni et al 2018 ; Strelets et al 2003 ; Tomescu et al 2014 ; Tomescu et al 2015 ), multiple sclerosis (Gschwind et al 2016 ), fibromyalgia (Gonzalez-Villar et al 2020 ), panic disorder (Kikuchi et al 2011 ), bipolar disorder (Damborska et al 2019 ; Vellante et al 2020 ), obsessive–compulsive disorder (Yoshimura et al 2019 ), depressive disorder (Murphy et al 2020b ), narcolepsy (Drissi et al 2016 ; Drissi et al 2019 ), stroke (Zappasodi et al 2017 ) or autism (D’Croz-Baron et al 2019 ; Jia and Yu 2019 ; Portnova et al 2020 ). EEG microstate analyses might therefore provide another tool for the development of a non-invasive assessment of healthy cognitive aging.…”
Section: Introductionmentioning
confidence: 99%
“…To explore this further, some studies have also mapped out the distribution of high alpha state durations ( Quinn et al, 2018 ). Such measures have been shown to correlate with motor and cognitive function in Parkinson’s disease ( Chu et al, 2020 ) and schizophrenia ( Khanna et al, 2015 ) and furthermore, cognitive manipulation of these states can be achieved through interventions ( Seitzman et al, 2017 ). However, no studies have used these dynamic parameters of alpha rhythm to measure neurophysiological changes in chronic pain.”…”
Section: Introductionmentioning
confidence: 99%